Forest Carbon Stock Measurement to Management: Perspective REDD+ in Bangladesh - Al-amin, M. (Indian Forester, 2016)
Quantification of the organic carbon stock of any forest area is impossible without estimating organic carbon storage of the forest. Presently, very scanty information is available about the organic carbon storage for forest areas of developing country like Bangladesh and thereby, a clear picture of organic carbon storage in the forests are yet to develop and the present study proposes a model of estimation of organic carbon of forest area based on their yield classes, as carbon content varies with the age of the species. Therefore, development of an allometric equation considering variables like yield class, species, age, site and exposures to hazard are necessary to estimate the carbon content of the species. Technological interventions i.e. applying remote sensing and GIS in measuring and managing carbon stock may facilitate in upcoming important event of forestry sector i.e. REDD+ and its MRV tasks to withstand the proper appraisal of carbon stock for present and future.